Sexual, Physical, and Emotional Maltreatment in Childhood Are Differentially Associated With Sexual and Physical Revictimization in Adulthood. Issue 3 (February 2023) - Rowe, Jessica; Chananna, Jasmine; Cunningham, Simone; Harkness, Kate L.
Childhood maltreatment increases risk for sexual and physical revictimization in adulthood. The goal of the current study was to examine whether this risk is associated with specific maltreatment types (i.e., sexual vs. physical vs. emotional maltreatment vs. neglect) and perpetrators (i.e., mother vs. father). Participants included 720 adult women from North America and the United Kingdom, recruited through the online platform Prolific Academic. The severity of childhood maltreatment and adult physical and sexual victimization were assessed in two separate sessions through self-report questionnaires. All maltreatment types were modeled together to account for their co-occurrence. Greater severity of sexual maltreatment was significantly and independently associated with greater risk for sexual, physical, and sexual + physical revictimization. Further, in the full sample, risk of revictimization was predicted by greater severity of father-perpetrated emotional and physical maltreatment. In contrast, in subgroup analyses focusing on plurisexual (i.e., bi/pansexual) women, risk of revictimization was predicted by greater severity of mother-perpetrated emotional and physical maltreatment. These results suggest that girls with sexual and emotional maltreatment histories are at highest risk for revictimization. Future research identifying the biological, psychological, and social sequelae of these specific exposures may enable the development of specific intervention programs that have the potential for maximum efficacy in preventing further violence against women most at risk.